已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},其中a≠b,M={x|x^2-2x-3≤0},①若CuB=M,求a,b的值,②若a〉b〉-1,求A∩B.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 11:09:03
已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},
已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},其中a≠b,M={x|x^2-2x-3≤0},①若CuB=M,求a,b的值,②若a〉b〉-1,求A∩B.
已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},
已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},其中a≠b,M={x|x^2-2x-3≤0},①若CuB=M,求a,b的值,②若a〉b〉-1,求A∩B.
已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},已知全集U=R,集合A={x|x^2+(a-1)x-a〉0},B={x|(x+a)(x+b)〉0},其中a≠b,M={x|x^2-2x-3≤0},①若CuB=M,求a,b的值,②若a〉b〉-1,求A∩B.
(x-3)(x+1)≤0 -1≤x≤3
a=-1或3
带入A得x^2+(-1-1)x+1=x^2-2x+1
x^2+(3-1)x-3=x^2+2x-3
可以得出a=3,那么b=-1
已知全集U=R,集合A={x|-2
已知全集U=R,集合A={X|-2
已知全集U=R,集合A=(x/x
已知全集U=R,集合A={x|x
已知全集U=R,集合A={x|x
已知全集U=R,集合A={x|x
已知全集U=R,集合A={x/x
已知全集U=R,集合A={x|x
已知全集U=R,集合A={x|-1
已知全集U=R,集合A={x|-1
已知全集U=R,集合A={x|0
已知全集U=R,集合A={x|0
已知全集U=R 集合A={x |-1
已知全集U=R,集合A={x|-7
已知全集U=R,集合A={x|0
已知全集U=R,集合A={X|-3
已知全集U=R,集合A={x|0
已知全集U=R 集合A={x |-1